Sistem Informasi Kepegawaian Pada Kantor Kecamatan Rambah Samo Berbasis Framework Laravel Fakultas Ilmu Komputer Universitas Pasir Pengaraian - Dona, Dona; Rifqi, Mi’rajul; Elfina, Yulia (Fakultas Sains & Teknologi, Universitas Labuhanbatu, 2024)
Promotion is an award given for work performance and dedication. Promotions must be given in a timely manner and to the right person. Promotions are given to civil servants at a higher level if concerned. At least 4 years late in the last level. The existing system at the Rambah Samo sub-district office, even though they are already using a computer, but for the process of completeness of files which often results in problems that arise related to promotion. that rank. problems that occur such as the number of employees who do not understand what files are proposed even though each period of the BKPP Kab. Rokan Hulu always sends letters regarding what files are prepared, many proposals are rejected because the period has not been calculated (not enough months). The programming language used in designing and implementing a personnel information system at the Rambah Samo District Office is PHP and the database used is MySQL. The results of research at the Rambah Samo District office, it can be concluded that this system is expected to assist the Rambah Samo District Office in managing promotion data and personnel data.